Effect of L-ascorbic acid on the monophenolase activity of tyrosinase. - Ros, J R (1993)
The effect of ascorbic acid on the monophenolase activity of tyrosinase, using tyrosine as substrate, has been studied. Over the ranges of ascorbic acid concentration used, no direct effect on the enzyme is found. However, a shortening of the characteristic induction period of the hydroxylation reaction is observed. The evolution of the reaction is dependent on the concentration of ascorbic acid. Low concentrations permit the system to reach the steady state when all ascorbic acid is consumed, whereas high concentrations do not. In the light of these results it is proposed that the influence of ascorbic acid on the reaction is due to its ability to reduce the enzymically generated o-quinones. A relationship between the ascorbic acid concentration, and the induction period generated by it, with the diphenolase activity of tyrosinase is established, which can be used as a basis for the determination of trace amounts of this reducing agent.